1998
DOI: 10.1023/a:1008074002390
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Analysis of 36 genotypes of finger millet (Eleusine coracana (L.) Gaertn) with varying seed colors revealed a wide range of protein and calcium contents. White seeded genotypes had higher protein contents, while brown seeded types had a wide range of values. The brown seeded genotype GE 2500 had the highest protein content. Although protein content had significant negative association with calcium content, white seeded types had moderate levels of calcium. The genotypic coefficients of variability were moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(20 citation statements)
references
References 1 publication
3
17
0
Order By: Relevance
“…The calcium average content of the prospected finger millets is 416.86 mg/100g which is consistent with Vadivoo, Joseph and Garesan (1998) results where the calcium content of 36 genotypes of finger millet ranged from 162 to 487 mg% with mean value of 320.8 mg%. Bhatt, Singh, Shrotria and Baskheti (2003) and Singh and Raghuvanshi (2012), reported that the finger has the highest calcium content among all cereals (344 mg/100g).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The calcium average content of the prospected finger millets is 416.86 mg/100g which is consistent with Vadivoo, Joseph and Garesan (1998) results where the calcium content of 36 genotypes of finger millet ranged from 162 to 487 mg% with mean value of 320.8 mg%. Bhatt, Singh, Shrotria and Baskheti (2003) and Singh and Raghuvanshi (2012), reported that the finger has the highest calcium content among all cereals (344 mg/100g).…”
Section: Discussionsupporting
confidence: 89%
“…The protein content of the accessions studied varied from 0.78 (GH3) to 11.88% (GH9) with a mean of 5.43%, which is consistent with the results sited by Singh and Raghuvanshi (2012) who reported that finger millet has nearly 7% protein, but large variations in protein content from 5.6 to 12.70% have been reported (Joshi & Katoch, 1990;Ravindran, 1991;Rao, 1994;Marimurthu & Rajagopalan, 1995;Antony, Sripriya, & Chandra, 1996;Vadivoo et al, 1998;Mushtari Begum, 1998;Gautam, 2000;Sharma, 2001;Bhatt et al, 2003). Chethan and Malleshi (2007) reported that finger millet contains about 5-8% protein.…”
Section: Discussionsupporting
confidence: 88%
“…In several studies on estimation of calcium content in different genotypes of finger millet, high calcium values have been reported. Calcium content varied from 162 to 487 mg/100 g with a mean value of 320.8 mg/100 g grain in 36 genotypes of finger millet (Vadivoo et al, 1998), 293–390 mg/100 g in six varieties of finger millet (Babu et al, 1987); 50–300 mg/100 g in another set of six varieties (Admassu et al, 2009). Furthermore, very high calcium content, 450 mg/100 g (Panwar et al, 2010) and 489 mg/100 g (Upadhyaya et al, 2011) has been reported in few finger millet genotypes.…”
Section: Plants: the Power House Of Calciummentioning
confidence: 99%
“…The morphological diversity present within finger millet is immense. For example, a range of seed colors can be produced, which are correlated with protein and calcium content (Vadivoo et al, 1998). Landraces with different attributes (e.g., time to maturity, bird tolerance, drought tolerance) are valued by farmers based on local agricultural complexities that reflect their productivity across multiple agro-economic zones (Tsehaye et al, 2006).…”
Section: Molecular Markers For Assessing Genetic Diversity Species Rmentioning
confidence: 99%